Nano selenium-doped TiO2 nanotube arrays on orthopedic implants for suppressing osteosarcoma growth - Hu, Xiaodong; Ke, Chunhai; Zhong, Jiaqi; Chen, Yujiong; Dong, Jieyang; Hao, Mingming; Chen, Qi; Ni, Jiahua; Peng, Zhaoxiang (Frontiers in Bioengineering and Biotechnology, 2023)
Osteosarcoma, the most common primary malignant bone tumor, is characterized by malignant cells producing osteoid or immature bone tissue. Most osteosarcoma patients require reconstructive surgery to restore the functional and structural integrity of the injured bone. Metal orthopedic implants are commonly used to restore the limb integrity in postoperative patients. However, conventional metal implants with a bioinert surface cannot inhibit the growth of any remaining cancer cells, resulting in a higher risk of cancer recurrence. Herein, we fabricate a selenium-doped TiO2 nanotube array (Se-doped TNA) film to modify the surface of medical pure titanium substrate, and evaluate the anti-tumor effect and biocompatibility of Se-doped TNA film. Moreover, we further explore the antitumor potential mechanism of Se-doped TNA film by studying the behaviors of human osteosarcoma cells in vitro. We provide a new pathway for achieving the anti-tumor function of orthopedic implants while keeping the biocompatibility, aiming to suppress the recurrence of osteosarcoma.